Differences in Handgrip Strength Between Statin Users and Non-users in Older Patients with Heart Failure. An Observational Retrospective Study of the PROFUND-IC Registry (Revista de Medicina Clinica, 2025)
Introduction: Heart failure is a chronic disease associated with different cardiovascular diseases. The management of this disease is based on the control of cardiovascular risk factors, in some cases, using different drugs, such as statins in the treatment of dyslipidemia. However, there are not enough studies evaluating the influence of statin use on muscle strength. Since frail elderly people may be more vulnerable to the side effects of statins, it would be of interest to evaluate the possible association between the use of statins and loss of muscle strength in patients with heart failure. Patients and Methods: We conducted an observational retrospective study including patients from the PROFUND-IC registry, which studied pluripathological patients hospitalized for acute heart failure. We described the different characteristics between statin users and non-users and compared handgrip strength between both groups. Results: A total of 476 patients were included, of whom 53.2% (253) had a median age of 84 years and were on statin therapy. Handgrip strength was pathological in 81% of statin users compared to 84.7% of non-users. Multivariate analysis showed no differences in handgrip strength between statin users and non-users, with an overall OR value of 1.036 (p = 0.94). Conclusion: Our study does not show an association between the use of statins and worse handgrip strength in older patients with heart failure. Therefore, frailty or older age should not be a limitation for the prescription of statins.
Keywords: Heart failure; Statin; Muscle strength; Frailty; Older adult